Introducing analytic philosophy : its sense and its nonsense, 1879-2002 - Hochberg, Herbert, 1929- (Logos (Frankfurt am Main, Germany), 2003)
Philosophy took a ""linguistic turn"" in the twentieth century that was marked by the focus on theories of meaning, reference, description, predication and truth. Starting with the roots of the analytic tradition in Frege, Meinong and Bradley, this book follows its development in Russell and Wittgenstein and the writings of major philosophers of the analytic tradition and of various lesser, but well known and widely discussed, contemporary figures. In dealing with basic issues that have preoccupied analytic philosophers in the past century, the author notes how analytic philosophy is sometimes.